Screen time and associated risks in children and adolescents with autism spectrum disorders during a discrete COVID-19 lockdown period - Berard, Mathilde; Peries, Marianne; Loubersac, Julie; Picot, Marie-Christine; Bernard, Jonathan Y.; Munir, Kerim; Baghdadli, Amaria (Frontiers in Psychiatry, 2022)
Background: The COVID-19 pandemic may affect the screen time of children and adolescents with Autism Spectrum Disorders (ASD). This study aimed to examine the screen time of children and adolescents with ASD during a discrete lockdown period in France and identify risk factors for excessive screen time. Method: The study sample consisted of 249 ASD subjects, 3-17 years of age, enrolled in the ELENA cohort. Information about the screen time was collected using the COVID-19 questionnaire specially created for this study. The clinical, socio-demographic and familial characteristics were collected from the last ELENA follow-up visit. Results: More than one third of subjects exceeded recommended levels of screen time and almost half of parents reported that their child spent more time using screen since COVID-19 pandemic beginning. Excessive screen time was significantly related to age with higher screen time in adolescents. Risk factors for excessive screen time were high withdrawn behaviors and low socioeconomic status for children, and older age and male gender for adolescents. Conclusions: These results imply to adapt the recommendations already formulated in general population concerning the good use of screens in youth with ASD. Specific recommendations and suitable guidance are needed to help children and adolescents with ASD and their parents implement the more optimal use of screen time activities for educational, therapeutic and social goals.